2022
DOI: 10.3233/wor-205100
|View full text |Cite
|
Sign up to set email alerts
|

Types of demands and well-being in correctional officers: The protective role of psychological capital

Abstract: BACKGROUND: Correctional officers’ personal resources, such as psychological capital (PsyCap), may help them better manage their work environment in the penitentiary; however, there is limited research on the relationship between indicators of well-being and types of demands in this cohort and whether this relationship depends on PsyCap. OBJECTIVE: The aim of this study was to examine three types of demands (job, personal, and group) and the effect of each on three indicators of low well-being: burnout, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Studies on a group of correctional officers have shown that selfefficacy as a component of psychological capital construct attenuates the effect of distress and negative team relations on low well-being indicators. At the same time, it is not a significant moderator between the work-family conflict and burnout or health complaints [65]. However, the previously published results may have been partially influenced by the adopted conception of SE (general vs. professional), between coping through stimulants and alcohol related behaviors.…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 73%
“…Studies on a group of correctional officers have shown that selfefficacy as a component of psychological capital construct attenuates the effect of distress and negative team relations on low well-being indicators. At the same time, it is not a significant moderator between the work-family conflict and burnout or health complaints [65]. However, the previously published results may have been partially influenced by the adopted conception of SE (general vs. professional), between coping through stimulants and alcohol related behaviors.…”
Section: O R I G I N a L P A P E Rmentioning
confidence: 73%
“…For the correction officers, WFC can be better addressed by allocating more time for family and receiving family relationship management courses [ 6 ]. Moreover, resilience can buffer the impact of WFC on burnout and anxiety, thus, it is crucial to identify protective factors that improve resilience and implement psychological interventions to promote resilience [ 60 ], such as mindfulness based intervention [ 61 ] and resilience training [ 62 ], which emphasizes problem-solving skills and the reduction of catastrophic thinking.…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of PsyCap can enable new nurses to maintain a positive and optimistic work attitude, think critically in their work, and facilitate the development of clinical thinking skills, thus promoting their professional growth [ 33 ]. Nurses with higher levels of PsyCap are more adept at coping with work-related stress, finding solutions in challenging situations, and are more likely to experience higher job satisfaction and adaptability, resulting in enhanced competence [ 34 ]. Therefore, nursing managers should focus on the cultivation and utilization of nurses’ motivation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%